2019
DOI: 10.1186/s13195-019-0497-9
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I deficiency increases cortical amyloid deposition, cerebral amyloid angiopathy, cortical and hippocampal astrogliosis, and amyloid-associated astrocyte reactivity in APP/PS1 mice

Abstract: Background Alzheimer’s disease (AD) is defined by amyloid beta (Aβ) plaques and neurofibrillary tangles and characterized by neurodegeneration and memory loss. The majority of AD patients also have Aβ deposition in cerebral vessels known as cerebral amyloid angiopathy (CAA), microhemorrhages, and vascular co-morbidities, suggesting that cerebrovascular dysfunction contributes to AD etiology. Promoting cerebrovascular resilience may therefore be a promising therapeutic or preventative strategy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 78 publications
(89 reference statements)
3
48
0
Order By: Relevance
“…Complete loss of ApoA-I increases cortical and hippocampal CAA pathology and astrogliosis in APP/PS1 mice, boosting both neuro and vascular inflammatory markers, specifically IL-1β, PDGFRβ, GFAP, and ICAM-1. These mice also showed an increase in GFAP-positive astrocytes associated with the cerebrovasculature [168]. ApoA-I could be an interesting target for a CAA-directed therapy as it was observed that APP/PS1 mice overexpressing ApoA-I or injection of ApoA-I reduced both astrogliosis and cerebral amyloid burden.…”
Section: Astrogliosis In Caamentioning
confidence: 94%
“…Complete loss of ApoA-I increases cortical and hippocampal CAA pathology and astrogliosis in APP/PS1 mice, boosting both neuro and vascular inflammatory markers, specifically IL-1β, PDGFRβ, GFAP, and ICAM-1. These mice also showed an increase in GFAP-positive astrocytes associated with the cerebrovasculature [168]. ApoA-I could be an interesting target for a CAA-directed therapy as it was observed that APP/PS1 mice overexpressing ApoA-I or injection of ApoA-I reduced both astrogliosis and cerebral amyloid burden.…”
Section: Astrogliosis In Caamentioning
confidence: 94%
“…On the contrary, a recent study using another transgenic mouse model of AD (Tg2576) showed that lack of APOA-I decreased both parenchymal and vascular Aβ pathology [86]. However, another recent study with APP/PS1 mice extended prior findings, in which APOA-I deficiency increased CAA and neuroinflammation as well as cortical Aβ deposition [87]. The differences between the AD animal models used and the ages of the mice studied may explain these discrepancies.…”
Section: Amyloid Pathologymentioning
confidence: 90%
“…APOA-I drives the critical role of HDL in cerebrovascular endothelial damage repair and inhibition of endothelial apoptosis [136]. Overexpression of human APOA-I mitigates CAA whereas lack of APOA-I exacerbates CAA in AD mouse models [83,84,87]. Moreover, pericytes, a key component in the BBB and the neurovascular unit, have recently emerged as a crucial regulator of vessel morphology and function [137,138].…”
Section: Cerebrovascular Functionmentioning
confidence: 99%
“…Epidemiological data suggest that HDL may protect against dementia, [76][77][78][79][80] and animal models show that low HDL levels lead to increased vascular amyloid and inflammation, while addition of that HDL can reduce CAA and soluble amyloid and brain Aβ levels. [81][82][83] While these studies suggest that HDL has a protective effect on cerebral vessels, key differences between mouse and human lipoprotein metabolism mean that these results need to be interpreted with caution. To understand how lipoproteins affect Aβ clearance across the arterial wall, Wellington's group has developed a bioengineered cerebrovascular model that incorporates many of the features of cerebral vessels, including an anatomically correct vascular anatomy, functional BBB, and dynamic perfusion.…”
Section: Cerebrovasculature Health In Alzheimer's Diseasementioning
confidence: 99%